2010
DOI: 10.1001/archdermatol.2010.132
|View full text |Cite
|
Sign up to set email alerts
|

Octocrylene, an Emerging Photoallergen

Abstract: Background: Octocrylene is a new emerging photoallergen. We report and discuss 50 cases of photoallergic contact dermatitis from octocrylene use and/or positive photopatch test reactions to this UV filter and draw attention to the unexpected association in adults with a history of photoallergic contact dermatitis from ketoprofen.Observations: Patients were divided in 3 groups: group A comprised 11 children; group B, 28 adults with a history of photoallergy from sunscreen products; and group C, 14 adults system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(108 citation statements)
references
References 11 publications
6
102
0
Order By: Relevance
“…However, this UV filter can be a strong allergen and can lead to contact dermatitis in children and adults (AvenelAudran et al, 2010). Avenel-Audran et al (2010) indicated that children and adults with a history of photoallergy from sunscreen products had positive patch and photopatch test reactions to OCR. In addition, Karlsson et al (2011) reported 23 cases of positive patch and photopatch test reactions in patients with a history of reaction to the anti-inflammatory drug ketoprofen.…”
Section: Synthetic Organic Uv Filtersmentioning
confidence: 99%
“…However, this UV filter can be a strong allergen and can lead to contact dermatitis in children and adults (AvenelAudran et al, 2010). Avenel-Audran et al (2010) indicated that children and adults with a history of photoallergy from sunscreen products had positive patch and photopatch test reactions to OCR. In addition, Karlsson et al (2011) reported 23 cases of positive patch and photopatch test reactions in patients with a history of reaction to the anti-inflammatory drug ketoprofen.…”
Section: Synthetic Organic Uv Filtersmentioning
confidence: 99%
“…Among the newer photoallergens, the NSAID ketoprofen not only induces severe and long-lasting photo-allergic contact dermatitis, but also gives rise to the development of photocontact allergy to the sunscreens benzophenone-3 and octocrylene. For reprint orders, please contact reprints@expert-reviews.com Special Report photodegradation [9,10]. These attractive properties have contributed to its widespread use in sunscreens and cosmetic preparations during the last 10 years and it is approved by the EU [102] and US FDA [11] in concentrations up to 10%.…”
Section: The Contact and Photocontact Allergen Octocrylenementioning
confidence: 99%
“…These attractive properties have contributed to its widespread use in sunscreens and cosmetic preparations during the last 10 years and it is approved by the EU [102] and US FDA [11] in concentrations up to 10%. The publications on positive patch and photopatch tests to octocrylene, a chemical UV filter, have increased over the past decade [9]. In the Department of Dermatology, University Hospital K.U.…”
Section: The Contact and Photocontact Allergen Octocrylenementioning
confidence: 99%
“…It was initially considered to be non-allergenic (Delplace & Blondeel, 2006). But even this agent has caused positive patch tests in 10 of 11 children tested (Avenel-Audran et al, 2010). Not all sunscreen ingredients that can cause allergy are active ingredients.…”
Section: Skin Care Products and Fragrancesmentioning
confidence: 99%